A novel ultrasonic cleaning tank developed by harmonic response analysis and computational fluid dynamics - Tangsopa, Worapol; Thongsri, Jatuporn (My University, 2020)
The manufacturer of an ultrasonic cleaning tank (UCT) received advise from a customer to seek the cause to why the UCT could not clean their products effectively and develop a novel UCT to replace the conventional model. This UCT had a capacity of 10 L, a frequency of 28 kHz, four horn transducers, and a total power of 200 W. To resolve that problem and respond to customers’ needs, we presented new methods to develop the UCT using the harmonic response analysis (HRA) and computational fluid dynamics (CFD) to simulate the cleaning process which occurred within the UCT based on the actual conditions. Results from the HRA showed that the acoustic pressure in a problematic UCT was low, resulting in a smaller cleaning area, which was consistent with the results from the foil corrosion test, and thus caused the cleaning process to be ineffective. We developed a novel UCT with improved effectiveness by adjusting the design and adding a water circulation system. From the HRA, we were able to design the dimensions of the UTC and position of the transducer to be suitable to increase the acoustic pressure and cleaning area. CFD results enabled us to design proper inlet and outlet shapes, as well as simulate the water flow behavior to find the optimal cleaning condition so the novel UCT had a water circulation system that could eliminate the excess particles.
Keywords: Acoustic pressure; Cavitation; Computational fluid dynamics; Harmonic response analysis; Piezoelectric transducer; Simulation; Ultrasonic cleaning